The Relationship Of Motivation And Performance Of Integrated Healthcare Center Cadres During The Covid-19 Pandemic On Basic Immunization Coverage In 2020 In The Working Area Of Bojongsari Public Health Center: Hubungan Motivasi Dan Kinerja Kader Posyandu Pada Masa Pandemi Covid-19 Terhadap Cakupan Imunisasi Dasar Tahun 2020 Di Wilayah Kerja Puskesmas Bojongsari - Ilmi, Ayatun Fiil; Adhana, Shelvia; Holidah, Holidah; Ratnaningtyas, Tri Okta (Jurnal Kesehatan Masa Depan, 2022)
Abstract Basic immunization is a mandatory immunization in the Puskesmas program where all babies aged over 12 months must have received basic immunization. Because basic immunization is made into a program so that existing diseases can be prevented by immunization. Immunization in the Puskesmas program has the aim of protecting children from disease, preventing disability in children, as well as preventing death in children. In Indonesia Complete Basic Immunization Coverage (IDL) decreased by 57.9%, incomplete immunization by 32.9% and 9.2% not immunized. The highest percentage was in Bali (92.1%) and the lowest was in Aceh (19.5%). (Ministry of Health 2018). The purpose of this study was to determine the relationship between motivation and performance of posyandu cadres during the covid-19 pandemic on immunization coverage in 2020 in the Bojongsari Health Center Work Area. The research method used is quantitative research with a case control. The sampling technique used was purposive sampling consisting of 42 respondents case and 42 resondents control. Data collection techniques using direct questionnaires. The results of data analysis in this study using the chi-square that the relationship between motivation and immunization coverage showed a significant p-value = 0.000, and the relationship between performance and immunization coverage showed a significant p-value = 0.000. Conclusion: there is a relationship between motivation and performance of posyandu cadres on immunization coverage. Suggestion: future researchers are expected to change the measurement method in the variables so that the measurement results are more effective. Keywords: Motivation; Performance; Immunization Coverage